Studies of transforming growth factor genes in cleft lip and palate in malays population - Roselinda, Ab Rahman (Pusat Pengajian Sains Perubatan, 2013)
Cleft lip with or without cleft palate and cleft palate alone are the most common craniofacial anomalies in Malaysia. Causes for clefting to happen are multi-factorial and a number of genes, including the transforming growth factor alpha (TGFa) gene, have been implicated in its etiology. TGFa gene has been proposed as a candidate genes in the aetiology of nonsyndromic cleft lip and palate based on previous studies on animals (Lee et al 1985, Dixon et al 1991 ). TGFa protein, epidermal growth factor and their receptors were expressed more intensely in regions of developing primary palate where ~ cell proliferation was most pronounced (lamaroon et al 1996). The role of TGFa gene in I lip and palatal development was also confirmed in human allelic association studies • (Ardinger et al 1989, Chevenic-Trench et al 1991, Holder et al 1992). We conducted a study on forty six Malay patients from Kelantan, Malaysia with non-syndromic cleft lip, cleft palate and combination of both cleft and analysed their blood for the (TGFa) gene polymorphism at locus Taq1 and compared it with thirty three control subjects. The results showed no significant difference between patients and controls. The presence of homozygous allele C1C1 was the most common in both cases and control, while ...) homozygous allele C2C2 was absent in both groups. In conclusion, we could not find any association between the TGFa Taq1 gene polymorphism and non-syndromic cleft lip with or without palate Malay patients from Kelantan Malaysia